2000
DOI: 10.1097/00001756-200012180-00022
|View full text |Cite
|
Sign up to set email alerts
|

High frequency repetitive transcranial magnetic stimulation (rTMS) of the dorsolateral prefrontal cortex in schizophrenic patients

Abstract: Repetitive transcranial magnetic stimulation (rTMS) has been tried therapeutically in major depression. In order to investigate the therapeutic efficacy of rTMS in psychotic patients, 12 participants (four women, eight men) with schizophrenia according to DSM-IV criteria, aged 25 to 63 years (mean (+/-s.d) 40.4+/-11.0), were enrolled in the study. Following a double-blind crossover design, patients were treated at random with 2 weeks of daily left prefrontal rTMS (20 2s 20 Hz stimulations at 80% motor threshol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
2
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 4 publications
2
61
2
9
Order By: Relevance
“…In a randomised, double-blind sham-controlled study high-frequency rTMS over the left dorsolateral prefrontal cortex (DLFPC) resulted in significant improvement compared to sham stimulation in the average BPRS score in 12 schizophrenic patients (Rollnik et al 2000;Huber et al 2003). Another study displayed a trend for a temporary improvement immediately after the application of a single verum 20 Hz rTMS session, persisting until the following day (Nahas et al 1999).…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%
“…In a randomised, double-blind sham-controlled study high-frequency rTMS over the left dorsolateral prefrontal cortex (DLFPC) resulted in significant improvement compared to sham stimulation in the average BPRS score in 12 schizophrenic patients (Rollnik et al 2000;Huber et al 2003). Another study displayed a trend for a temporary improvement immediately after the application of a single verum 20 Hz rTMS session, persisting until the following day (Nahas et al 1999).…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%
“…[53][54][55][56] The findings were relatively promising; however, the findings were controversial. A meta-analysis review of nine clinical trials (n = 213 patients) showed that active rTMS could significantly improve the negative symptoms of schizophrenia compared with the sham rTMS.…”
Section: Schizophreniamentioning
confidence: 99%
“…Rollnik et al examined, in a double-blind, crossover design, the effects of higher frequency rTMS delivered to left prefrontal cortex in 12 schizophrenia patients with negative symptoms [13]. In this study, rTMS was delivered to left DLPFC each day for 2 weeks.…”
Section: Effect Of Rtms On Negative Symptomsmentioning
confidence: 99%